Case Series of Rare Head and Neck Plasmacytoma: Experiences in Indonesia - Maya Sofa; Maman Abdurahman; Kiki A. Rizky; Yohana Azhar; Bethy Hernowo; Adji Kusumadjati; Monty P. Soemitro (HM Publisher, 2023)
Background: Solitary plasmacytoma (SP) is a rare case of plasma cell neoplasms, which only represent 5-10% of all plasma cell neoplasms that afflict two or three people per every 100,000 of the general population. This neoplasm is divided into solitary plasmacytoma of the bone (SBP) and solitary extramedullary plasmacytoma (SEP), depending on the location. Due to the rarity, SBP can be misdiagnosed as multiple myeloma (MM) while SEP as plasma cell granuloma, whereas the treatments are very different. This study aimed to present our experiences in diagnosing SP in the head and neck to differentiate them from MM and plasma cell granuloma. Case presentation: One case of multiple solitary plasmacytomas of the bone (SPB) in the frontal bone and one case of intraoral solitary extramedullary plasmacytoma (SEP) were presented. The SBP showed abnormality in the laboratory and the CT showed a punch-out lesion which is similar to MM. The SEP showed normal laboratory findings, but the histopathology mimicked plasma cell granuloma. Both immunohistochemistry was positive for CD138, and the SEP diagnosis was confirmed by Ki67 and κ-light chain. Complete examination from history taking, physical examination, radiology and laboratory findings, bone marrow morphology, and histopathology including immunohistochemistry examination, are very important to determine the correct diagnosis. Conclusion: the case was diagnosed as head and neck solitary plasmacytoma.